The Sericothripinae genus Neohydatothrips (Thysanoptera, Thripidae) in India with description of two new species - Tyagi, Kaomud; Kumar, Vikas (Zootaxa, 2016)
Two new species of Neohydatothrips are described from India, N. chandrai and N. plumeria. The former was collected on leaves of a hedge plant in northwest India, and the latter on flowers and leaves of Plumeria sp. in eastern India. A key to the seven species of Neohydatothrips recorded from India is also provided. Partial sequence data of mitochondrial cytochrome c oxidase (mtCOI) from the holotypes of each of these two new species were generated.